The Challenges of Strategic HRM in the Thai Higher Education Sector - Kowsuvon, Kunsiree (Curtin University, 2023)
The central aim of this research is to investigate the extent to which SHRM policies and practices are present in the Thai higher education system. This research will utilise a qualitative research methodology and a case study approach. The expected research outcomes include: 1) understanding how HRM practices are developed and implemented, 2) assessing the link between HRM programmes and the HR challenges facing Thai universities, 3) making recommendations regarding HR programme design and implementation.